Adults’ acceptance of covid-19 vaccine for children in selected lower-and middle-income countries - Suzanna Awang Bono (2022)
Since emergency approval of COVID-19 vaccines for children aged between 12 and 15 years old was recently obtained in the United States and Europe, we aimed to assess the willingness to vaccinate children with a COVID-19 vaccine in lower-and middle-income countries (LMICs). Therefore, we launched an online cross-sectional survey in several LMICs. Questions relating to socio-demographic information, knowledge of COVID-19, level of fear/worry of being infected with COVID-19, and willingness to vaccinate children with the COVID-19 vaccine at 50%, 75% and 95% effectiveness levels, were asked. Of the 6571 participants (mean age = 39 ± 14 years), 64.0%, 72.6%, and 92.9% were willing to vaccinate children at 50%, 75%, and 95% effectiveness levels, respectively. Respondents who were undergraduates, who were more worried/fearful about COVID-19, had higher knowledge scores regarding COVID-19, and a higher belief that COVID-19 vaccination is important to protect others, were more willing to accept COVID-19 vaccination of children. COVID-19 vaccination of children will limit the spread of the virus, especially in schools; it may decrease the need for school closures which has a negative effect on child development. Findings from this study are useful for health promotion strategies during COVID-19 vaccination implementation among children in LMICs.